IMPLEMENTASI PENILAIAN HASIL BELAJAR SECARA DIGITAL BERBASIS APLIKASI E-RAPOR UNTUK DOKUMENTASI AKADEMIK - Insan, Pramudya Prima; Idris, Nasruddin Bin; Kharisma Mahardika, Muhammad (Information Technology Education Department, 2024)
The report card is an important student learning outcome value, the purpose of holding a report card is as a communication link from the school to the parents of students so that they can find out the results of their children's learning achievements during each semester. Assessment of learning outcomes by educators aims to monitor and evaluate the process, learning progress, and improvement of student learning outcomes on an ongoing basis. The process of assessing student learning outcomes, both by educators and by education units, will be more systematic, comprehensive, more accurate, and faster if supported by computer application tools. Regarding the limited electronic equipment and the lack of knowledge of teachers in computer knowledge in schools, it does not mean that they make an excuse not to apply the report card application in student assessment. How to design an application for digital student academic documentation in a school. Research needs that intend to understand the phenomenon of what is experienced by the research subject holistically and by way of description in the form of MVT Django Framework implementation. The results of research, analysis, modeling and implementation of MVT in the E-Report application were successfully made with the data management process including the conclusion that the MVT structure in the Django framework clearly separates different tasks, and the use of Model, View, Template in the Django framework helps in designing and developing web-based applications that are structured, efficient, and easy to maintain and update. With this E-Report application, the management of learning outcomes data for all students can be done electronically storing academic data because it can print E-Report documents and schools can document student learning outcomes digitally.